Girls and boys: Economic crisis, fertility, and birth outcomes. (6th August 2018) - Lee, Soohyung; Orsini, Chiara
Summary: We investigate the impact of an economic downturn on natality and birth weight for newborns when parents prefer sons. We examine South Korea, unexpectedly hit by the Asian financial crisis in 1997. For identification, we exploit regional and time variation in the crisis, focusing on women who were already pregnant when the downturn began. We find that the number of girls would have been 2% higher absent the crisis and that birth outcomes for girls were no better than those for boys—findings that differ from the Trivers–Willard Hypothesis. This relative disadvantage of girls is more severe among newborns who have at least two older siblings.